Polymer Injection Modeling in a Solution Gas Drive-Naturally Fractured Reservoir - Widiyaningsih, Indah; Helmy, Mia Ferian; Kaesti, Edgie Yuda; Arta, Atma Budi (Universitas Pembangunan Nasional Veteran Yogayakarta, 2021)
Solution Gas Drive-Naturally Fractured Reservoir (NFR) has relatively high remaining oil reserves. This causes less optimum oil from the reservoir to be produced to the surface, so that it requires an enhanced oil recovery (EOR). EOR can be done by chemical injection, one of which is by polymer injection. Polymer injection emphasizes improving the swept efficiency. The most important parameter in this case is the mobility ratio. The injection process is very dependent on reservoir fluid characteristics, rock heterogeneity, and interactions between fluid and rock. Therefore, studies are needed to understand the mechanism of polymer injection that occurs in the reservoir.Simulation modelling of polymer injection on solution gas drive naturally fractured carbonate reservoir will be done using a black-oil simulator. In the black oil simulator it can be observed changes in the parameters of the mobility ratio of water to oil. In this simulation will run water flooding case as comparison to polymer injection case.The purpose of this study is to observe an increase in recovery factor with water flooding and polymer injection scenario on solution gas drive-NFR. The scenario that provides the greatest recovery factor can be considered in carrying out a strategy to increase oil recovery at EOR methods.